Microangiopathic haemolytic anaemia with thrombocytopenia induced by vitamin B12 deficiency long term after gastrectomy - Harada, Yukinori (BMJ Case Rep, 2018)
Microangiopathic haemolytic anaemia with thrombocytopenia, called pseudo-thrombotic microangiopathy (TMA), is a clinically important complication in patients with vitamin B12 deficiency. We herein present a case of an 80-year-old woman with pseudo-TMA after gastrectomy. She was initially suspected with thrombotic thrombocytopenic purpura based on rapid progression of anaemia with schistocytes and thrombocytopenia; however, her anaemia and thrombocytopenia were improved by vitamin B12 supplementation alone, with a single session of plasma exchange. Vitamin B12 deficiency was finally confirmed by low vitamin B12 levels from the patient’s initial blood sample. In addition, normal ADAMTS13 activity was proven, lowering the likelihood of thrombotic thrombocytopenic purpura. Therefore, this patient was diagnosed with pseudo-TMA caused by vitamin B12 deficiency. Pseudo-TMA can occur in patients with vitamin B12 deficiency post-gastrectomy.